Febrile Urinary Tract Infections in Children: The Role of High Mobility Group Box-1 - Roberto Chimenz; Valeria Chirico; Caterina Cuppari; Alessia Sallemi; Davide Cardile; Sergio Baldari; Giorgio Ascenti; Paolo Monardo; Antonio Lacquaniti (MDPI AG, 2022)
Background: Differentiating between febrile lower urinary tract infection (LUTI) and acute pyelonephritis (APN) is crucial for prompt clinical management. We investigated whether the high mobility group box-1 (HMGB1) could be a useful biomarker in differentiating between LUTI or APN. Methods: We enrolled seventy-four pediatric patients with suspected LUTI/APN, according to the positive or negative renal scintigraphy (DMSA) scan. If the first DMSA findings were abnormal, a second DMSA was performed after six months. Voiding cystourethrography ruled out vesicoureteral reflux (VUR). Results: Higher serum (s) HMGB1 levels characterized the APN group when compared to LUTI patients (13.3 (11.8-14.3) versus 5.9 (5.2-6.8) ng/mL, p: 0.02), whereas there were no differences according to urine (u) HMGB1 values. sHMGB1 correlated with C-reactive protein (CRP) levels (β = 0.47; p: 0.02). Receiver operating characteristic curves identified the best diagnostic profile for detecting APN. sHMGB1 area under the curve was different from CRP (p: 0.01) and white blood cells (p: 0.003). After multivariate analyses, VUR (HR:4.81) and sHMGB1 (HR 1.16; p: 0.006) were independently associated with the risk of renal scarring development. Conclusions: sHMGB1 could represent a marker to differentiate APN from LUTI. Measurement of sHMGB1 could select children for early intervention or long-term follow-up.